Development of new injector for compressed natural gas engine and the effect on performance - Semin, Semin (2011)
This thesis deals with the experimental and computational assessment of a new injector nozzle for a sequential port injection CNG engine. The objective of this thesis was to develop, analyse and investigate the performance characteristics of a new injector nozzle. The methodology of this study was to convert a diesel engine to a CNG engine with modifications the piston and enhancements the spark ignition and throttle based on computational design using GT-Power and experimental results using an eddy current dynamometer. Next, a simulation of the fuel flow of the new injector nozzle was made using Cosmos FloWok. The final objective was to investigate the performance characteristics of the CNG engine using the new injector nozzle. The investigation focused on engine performance based on variations in engine speed. The engine experiments were conducted according to ISO 3046 for reciprocating internal combustion engine performance. The results showed that the conversion of the diesel engine to a CNG engine reduced engine performance. The simulation of the fuel flow of the new injector nozzle increased the spray distribution, fuel-air mixing and fuel flow velocity. The performance characteristics of the new injector nozzle increased the CNG engine’s performance and reduced its fuel consumption compared to the original injector. In conclusion, this study reports that the improvement of a new injector nozzle for a CNG engine significantly increased the engine’s performance and fuel consumption.